Efecto del fertilizante orgánico, inorgánico más micorrizas en la producción de biomasa y contenido nutricional de la pastura de Brachiaria decumbes en la zona de Nanguipa Alto cantón Centinela del Cóndor - Cuenca Angamarca, Julia Apolina (2024)
In Ecuador, livestock farming is essential within the agricultural sector, providing many families with economic support, in the same way in the last decade due to the increase in population, the consumption of food of bovine origin has been increasing, which has caused the expansion of the border of production of pastures for animal feed, especially in the Ecuadorian Amazon. The low yield and poor nutritional value of pastures leads the farmer to look for new alternatives for pasture improvement. Brachiaria decumbes is the pasture that is present and with greater extension the study area due to its great capacity for adaptation, however, its performance is not optimal due to the nutritional deficiencies of the place. The present study allowed us to evaluate the interaction of organic and inorganic fertilizer plus mycorrhizae in a previously established pasture. The trial was carried out in the area of Nanguipa Alto, Sentinel of the Condor canton, with a Split Plot Design (DPD) with a completely randomized block structure with 6 treatments and 4 repetitions, with a total of 24 experimental units.T1 (Mycorrhiza plus organic fertilizer), T2 ((Organic fertilizer), T3 (Mycorrhiza plus inorganic fertilizer), T4 (Inorganic fertilizer), T5 (Mycorrhiza), T6 (Witness). The variables height, number of leaves per macollo, number of chunks, stem diameter were taken every 15 days after the equalization cut, while the plant cover and the production of green matter was taken after 45 days when the equalization cut was made parallel to the variables of the nutritional content. The ANOVA statistical analyses and comparison test were carried out in the InfoStat program. The pasture reached a height of 73.69 cm with T3 at 45 days after the equalization cut. On the other hand, the best production of green material (MV) was also achieved by T3 with a production of 30, 51 TN/Ha of MV. In the variables of the nutritional content there is no significant difference between the treatments, but in general T3 predominates in relation to the other treatments.